2007
DOI: 10.1177/154405910708601214
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Gene Expression by Human Periodontal Ligament Cells under Cyclic Tension

Abstract: The forces that orthodontic appliances apply to the teeth are transmitted through the periodontal ligament (PDL) to the supporting alveolar bone, leading to the deposition or resorption of bone, depending upon whether the tissues are exposed to a tensile or compressive mechanical strain. To evaluate the osteogenic potential of PDL cells, we applied a 12% uni-axial cyclic tensile strain to cultured human PDL cells and analyzed the differential expression of 78 genes implicated in osteoblast differentiation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 37 publications
7
119
0
1
Order By: Relevance
“…Based on the belief that this protein may be a mineralization inhibitor and the fact that the PDL is "sandwiched" between two mineralized tissues, cementum and alveolar bone, it is tempting to think that this protein may be important in preventing PDL from being mineralized. It might provide valuable information about the role of FAM20C as we examine whether the inactivating mutations in the FAM20C gene, as in the case of lethal osteosclerotic bone dysplasia, may result in tooth ankylosis in these patients (Wescott et al 2007) or in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the belief that this protein may be a mineralization inhibitor and the fact that the PDL is "sandwiched" between two mineralized tissues, cementum and alveolar bone, it is tempting to think that this protein may be important in preventing PDL from being mineralized. It might provide valuable information about the role of FAM20C as we examine whether the inactivating mutations in the FAM20C gene, as in the case of lethal osteosclerotic bone dysplasia, may result in tooth ankylosis in these patients (Wescott et al 2007) or in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, tension applied to the tooth causes newly alveolar bone to form in the tension side (4). Indeed, 12% uni-axial cyclic tension increases the expression of ALP (7). However, other studies show that cyclic tension decreases ALP activity (8).…”
Section: Introductionmentioning
confidence: 96%
“…These results suggested an involvement of an ERK1/2-dependent pathway in the ephrin-B2-dependent regulation of Runx2 in osteoblasts. Increased ALP transcription was accompanied by an increase in Ephrin-B2-Fc Induces Runx2 and ALPL Transcription in PDLF-Subpopulations of PDLF have been reported to be able to express osteoblast-specific genes (14) and might contribute to osteogenesis at tension sites in orthodontic tooth movement. Here, we showed that mechanical strain in PDLF induces the expression of ephrin-B2.…”
Section: Ephrin-b2-fc Activates Runx2 and Alp Transcription In Osteobmentioning
confidence: 99%
“…Fibroblasts within the PDL are the first cellular recipients of mechanical strain. Under cyclic strain, PDL fibroblasts in vitro increased their osteogenic gene expression (14). An in vivo model of tooth movement indicated enhanced expression of Runx2 and the phosphorylation of extracellular signal-regulated kinases 1/2 (pERK1/2) under tension (15).…”
mentioning
confidence: 99%